2009
DOI: 10.1007/s10126-008-9174-x
|View full text |Cite
|
Sign up to set email alerts
|

Enriching Rotifers with “Premium” Microalgae. Nannochloropsis gaditana

Abstract: The nutritive quality of Nannochloropsis gaditana cultured semicontinuously with different daily renewal rates was tested as a diet for short-term enrichment of the rotifer Brachionus plicatilis. After 24 h, dramatic differences in the survival, dry weight, and biochemical composition of the rotifers depending on the renewal rate of microalgal cultures were observed. Survival after the feeding period increased with increasing renewal rates. Rotifers fed microalgae from low renewal rate, nutrient-deficient cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…Several Nannochloropsis species have been studied as candidate production strains in large-scale biofuel facilities because of their hardy outdoor growth profiles and high lipid yields (4)(5)(6)(7)(8)(9). They are also producers of valuable pigments (10) and nutritive oils (11,12) and are commonly used as an aquaculture feed (13).…”
mentioning
confidence: 99%
“…Several Nannochloropsis species have been studied as candidate production strains in large-scale biofuel facilities because of their hardy outdoor growth profiles and high lipid yields (4)(5)(6)(7)(8)(9). They are also producers of valuable pigments (10) and nutritive oils (11,12) and are commonly used as an aquaculture feed (13).…”
mentioning
confidence: 99%
“…Examples of commonly used microalgae and yeast include the microalgae Nannochloropsis (Fukusho, 1989;Kostopoulou and Vadstein, 2007;Ferreira et al, 2009), Chlorella (Maruyama et al, 1997;Cabrera et al, 2005;Zhou et al, 2009), and Nannochloris (Witt et al, 1981;Hur, 2001, Cho et al, 2007), and the yeasts bread yeast Saccharomyces cerevisiae (Gilberto and Mazzola, 1981;Sarma et al, 2002;Wang et al, 2009) and marine yeast Candida utilis (Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Striped mullet and milkfish fed rotifers grown on yeast have lower survival than fish fed rotifers that are grown on microalgae or a combination of microalgae and yeast. Ferreira et al, (2009) reported that Nannochloropsis sp. is widely used for rotifer production since it supports higher growth rates than baker's yeast and provides the rotifers with high amounts of EPA.…”
Section: Discussionmentioning
confidence: 99%
“…HUPArich microalgae such as Isochrysis and Pavlova contain high DHA levels and can be fed to B. plicatilis for DHA enrichment, which results in DHA/EPA ratios above 2.0 (Hemaiswarya et al, 2011). However, the nutritional value of baker's yeast (as not laborious, not time consuming and not expensive diet for rotifer) may be enhance easily by adding of marine oil enrichment, especially EPA and DHA that are needed for all marine larvae (Ferreira, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation